Investing in crises - Matthew Baron; Luc Laeven; Julien Pénasse; Yevhenii Usenko (European Central Bank (ECB), 2021)
We investigate asset returns around banking crises in 44 advanced and emerging economies from 1960 to 2018. In contrast to the view that buying assets during banking crises is a profitable long-run strategy, we find returns of equity and other asset classes generally underperform after banking crises. While prices are depressed during crises and partially recover after acute stress ends, consistent with theories of fire sales and intermediary-based asset pricing, we argue that investors do not fully anticipate the consequences of debt overhang, which result in lower long-run dividends. Our results on bank stock underperformance suggest that government-funded bank recapitalizations can often lead to substantial taxpayer losses.
Keywords: G11; G14; G15; G41; 330; investments; financial crises; returns; fire sales